The Geography of Displacement, Refugees’ Camps and Social Conflicts - Coniglio, Nicola Daniele; Peragine, Vitorocco; Vurchio, Davide (World Bank, Washington, DC, 2022)
The aim of this paper is twofold. Firstly, the authors analyze the geographical dimension of refugee camps in Africa by shedding light on the heterogeneous location patterns of hosting camps across countries as well as the economic settings in which refugee camps are situated, which allows us to identify the main determinants of such patterns. Second, the authors investigate the effects of hosting refugees in camps on the occurrence of protests and social conflicts, by using geo-referenced panel data from a large sample of African countries between 2000 and 2014. The main analysis is performed by using 50x50 km cells as units of analysis, GDELT and GED data on the frequency of protests, armed conflicts and other organized violence events and data from UNHCR Camp Mapping Database. By using a counterfactual empirical strategy, the authors find that refugee camps significantly increase the occurrence of protests only in the first two years while no significant effect is detected in the subsequent years. The authors do not find evidence of any effect of camps location on the frequency of violence events resulting in casualties. Moreover, by performing a highly detailed analysis with GHSL data the authors find that the presence of camps on average positively affects economic growth.